SOSIALISASI PEMUTAKHIRAN PENULISAN KARYA ILMIAH BAGI MAHASISWA PENDIDIKAN AGAMA ISLAM UNIVERSITAS ALMA ATA - Nur Kholik (Indonesian Collaboration Journal of Community Services, 2023)
It is known that some of the activities of the PAI Study Program include organizing socialization of "thesis writing", where the activities are focused on research activities as well as distributing information to students related to thesis cheating style. The service procedure is through several things, namely: 1) understanding of participants, 2) mastery of the layout of writing and systematics of scientific papers, 3) understanding of planning, 4) implementation of methods, 5) evaluation. Then the results of the evaluation of activities produced several conclusions including; a) The activity was well organized attended by the Head of Study Program, presenters and 98 students who were compiling a thesis, b) The results of the evaluation found that students had understood and received information about the systematics of writing and thesis cheating style at Alma Ata University, 3) Students felt that they had additional knowledge related to their research methodology, d) Students were motivated to compile a thesis, e) Students have understood the technique of compiling research articles as a graduation requirement at neighborhood of Alma Ata University